2009
DOI: 10.1007/s12560-009-9020-y
|View full text |Cite
|
Sign up to set email alerts
|

Capsid and Infectivity in Virus Detection

Abstract: The spectacular achievements and elegance of viral RNA analyses have somewhat obscured the importance of the capsid in transmission of viruses via food and water. The capsid’s essential roles are protection of the RNA when the virion is outside the host cell and initiation of infection when the virion contacts a receptor on an appropriate host cell. Capsids of environmentally transmitted viruses are phenomenally durable. Fortuitous properties of the capsid include antigenicity, isoelectric point(s), sometimes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…However, viral RNA detection by RT-PCR was necessary to understand the disinfection mechanism employed by underwater arc treatment, as both the viral genome and its capsid are required for virus infectivity (Cliver, 2009). In this study, the RT-PCR results demonstrated that genomic damage of MNV-1 RNA caused by underwater arc treatment was observed, although the level of genomic damage was underestimated in comparison with the inactivation effect detected using culture methods.…”
Section: Changes In the Copy Number In An Rt-pcr Assay Of Mnv-1 Genommentioning
confidence: 78%
“…However, viral RNA detection by RT-PCR was necessary to understand the disinfection mechanism employed by underwater arc treatment, as both the viral genome and its capsid are required for virus infectivity (Cliver, 2009). In this study, the RT-PCR results demonstrated that genomic damage of MNV-1 RNA caused by underwater arc treatment was observed, although the level of genomic damage was underestimated in comparison with the inactivation effect detected using culture methods.…”
Section: Changes In the Copy Number In An Rt-pcr Assay Of Mnv-1 Genommentioning
confidence: 78%
“…Though some of the antiviral mechanisms of action of plant antimicrobials may be shared between enveloped and nonenveloped viruses, others may be unrelated. To some extent, antimicrobials that inactivate small enteric RNA viruses such as the picornaviruses (e.g., poliovirus and hepatitis A virus), astroviruses, and caliciviruses (e.g., NoV and MNV) all act on the virus capsid (95). The capsid in such nonenveloped viruses serves to protect the integrity of the viral nucleic acid and to initiate infection by adsorbing to the host cell (95).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis predicts that PMA will only be able to distinguish between infectious and noninfectious viral particles when the inactivation conditions result in a sufficiently damaged capsid. Effective damage could be due to physical loss of capsid protein or to conformational changes the expose the nucleic acid (Cliver, 2009). Due to the importance of human NoVs in waterborne disease, the present study uses MNV-1 as a model to evaluate PMA for selective differentiation of infectious and non-infectious NoVs.…”
Section: Q3mentioning
confidence: 99%